FINANCIAL PERFORMANCE ANALYSIS AT PT. ADHI KARYA (PERSERO) TBK ON THE INDONESIAN STOCK EXCHANGE - Arif Imam; Abd Rahman Laba; M Sobarsyah (Paulus Journal of Accounting (PJA), 2023)
This study aims to determine the financial performance of PT. Adhi Karya (Persero) Tbk. This financial performance assessment is according to the Decree of the Minister of BUMN Number: Kep 100/MBU/2002, used to assess its financial performance. The population in this study is the financial statements of PT. Adhi Karya (Persero) Tbk. obtained through the Indonesian Stock Exchange website for the last five years' (2015–2020), while the samples are the balance sheets and income statements for the last six years (2015–2020). Data collection in this research involves documentation and data analysis techniques using ratios. Based on the findings of the evaluation of the financial aspect's soundness level, it is evident that PT. Adhi Karya (Persero) Tbk. for the 2015–2020 period In 2015, the total score (weight) obtained was 48 in the BB category, which is unhealthy criteria. Then in 2016, the total score (weight) obtained was 38.25 for category B, unhealthy criteria. In 2017, the total score (weight) obtained was 41.25 in the BB category with unhealthy criteria; in 2018, the total score (weight) was 43.25 in the BB category with unhealthy criteria. Then in 2019 a total score (weight) was obtained, namely 39.5 with category B, unhealthy criteria. Then in 2020, a total score (weight) of 28.75 was obtained in the CCC category with unhealthy criteria.